PENGARUH BUDAYA ORGANISASI DAN MUTASI PEGAWAI TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERATOR MELALUI KOMITMEN ORGANISASI PT ANGKASA PURA I (PERSERO) - Aditianto, Dian; Sihite, Mombang; Supriyadi, Edy (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2020)
The purpose of this study was to determine the effect of corporate culture, mutation towards employess’s performance trhough organizational commitmen with motivation as a moderating variable. The population of this research is 450 people with the level manager until senior manager in PT Angkasa Pura I (Persero). The number of samples of the population was 212 people taken using clutering purposive sampling technique. The statistical method used in this study is Structural Equation Modeling (SEM) which is operated through the WarpPLS 7.0 program. In this study, the results showed that the variables of corporate culture, mutation have positive and significant influences towards employess’s performance trhough organizational commitmen. The role of motivation can moderate the employee’s performance, meanwhile the variabel of mutation have unsignificant influence toward employee’s performance.